Contextual Teaching and Learning Models in Improving Learning Motivation and Communication Skills of Students in the Social Sciences Subject at Tadulako Sports Public High School - Appia Nita Tungka; Misnah; Idrus Rore; Juraid Abdul Latif (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Knowledge social is the object of science, his research is society, or always human capricious. Because the characteristic is always a society variable, up to now Not yet can be investigated and analyzed in a complete manner the connection between the elements inside the public in a deeper manner. To know social knowledge in a concrete manner is, what is to be the center of the study. one _ quite a way easy For earn characteristics something knowledge knowledge is with method paint it in a concrete manner . As for objective study This is Analyze CTL model implementation in increasing motivation Study participant students in class X SMANOR Tadulako on the learning process IPS family. Analyze the CTL model implementation to increase the ability to communicate participant students in class X SMANOR Tadulako on the learning process of the IPS family. Approach used _ on study This is a type of study descriptive in qualitative nature about motivation Study And the ability of communication of participants to educate through the implementation of the CTL learning model. the data that has been obtained on the results of the study is the data from the results of observations or observations made by the social studies group teacher (economics, sociology, geography, history), head school researcher, and student XC class. Observations made aim To know the circumstances at the moment the application of the CTL model of various eye subjects deep IPS families implementing the CTL model capable teachers know the ability of students to communicate and see motivation Study students in the application of the CTL model.